The Impact of Oxytocin Administration on Charitable Donating is Moderated by Experiences of Parental Love-Withdrawal - Van Ijzendoorn, Marinus H.; Huffmeijer, Renske; Alink, Lenneke R.; Bakermans-Kranenburg, Marian J.; Tops, Mattie (Frontiers in Psychology, 2011)
Oxytocin has been implicated in a variety of prosocial processes but most of this work has used laboratory tasks (such as the ultimatum game or the dictator game) to evaluate oxytocin’s prosocial effects. In a double blind randomized trial we examined the influence of intranasal administration of oxytocin on real, high-cost donating money to a charity without any expectation for reciprocation. Participants in the current study were 57 female undergraduate students, aged 18–30 years, who received a nasal spray containing either 24 IU of oxytocin or a placebo, and were then given the opportunity to make a charitable donation. The participants reported how often their parents used love-withdrawal as a disciplinary strategy involving withholding love and affection after a failure or misbehavior. Oxytocin appeared to increase the participants’ willingness to donate money to a charity but only in participants who experienced low levels of parental love-withdrawal. In contrast, oxytocin administration was ineffective in enhancing donating behavior in individuals who experienced high levels of parental love-withdrawal. We conclude that the positive effect of oxytocin administration on prosocial behavior may be limited to individuals with supportive backgrounds.